2010
DOI: 10.1007/s11145-010-9255-x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the scrambling complexity hypothesis in sentence processing: a self-paced reading study on anomaly detection and scrambling in Hindi

Abstract: The scrambling complexity hypothesis based on working memory or locality accounts as well as syntactic accounts have proposed that processing a scrambled structure is difficult. However, the locus of this difficulty in sentence processing remains debatable. Several studies on multiple languages have explored the effect of scrambling on sentence processing and not all languages have shown an advantage for the canonical word order. Using a self-paced reading paradigm, we studied the effect of scrambling on seman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…S-V-O). This also has a resemblance to other data from Hindi, where the non canonical SVO pattern has been found to be less depending in processing Mishra, Pandey & Srinivasan, 2011). However, at this point of time, without further controlled studies, this approach remains as a hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…S-V-O). This also has a resemblance to other data from Hindi, where the non canonical SVO pattern has been found to be less depending in processing Mishra, Pandey & Srinivasan, 2011). However, at this point of time, without further controlled studies, this approach remains as a hypothesis.…”
Section: Discussionsupporting
confidence: 79%
“…This preference is reflected in increased reading times behaviourally, and neurocognitively in an increased centro-parietal positivity (the P600) for ungrammatical SOV but not for ungrammatical SVO (Weyerts et al, 2002). Studies have also shown processing difficulties that language users experience when dealing with correct but less frequently occurring word orders (Fiebach, Schlesewsky & Friederici, 2002; Friederici, Hahne & Saddy, 2002; Friederici, Steinhauer, Mecklinger & Meyer, 1998; Rösler, Pechmann, Streb, Röder & Hennighausen, 1998; Vos, Gunter, Schriefers & Friederici, 2001; but see Mishra, Pandey & Srinivasan, 2011; Yamashita, 1997). Examples of such word orders include scrambling, such as German dislocations where an object can appear in a pre-subject position sentence-medially with overt case-marking, as in the sentence Maria glaubt, dass den Onkel [O] der Vater [S] schlägt .…”
Section: Native Word Order Processingmentioning
confidence: 99%
“…Comrie (1981) defined canonical word order as the statistically most frequent order, which is also the neutral order in a given discourse context. The comprehension of non-canonical word orders has been investigated in the Hindi sentence comprehension literature (Vasishth 2004, Mishra et al 2011, Choudhary 2011. In addition, works on Hindi and other verb-final languages have revealed role of information status considerations in preverbal constituent ordering (Butt andKing 1996, Ferreira andYoshita 2003).…”
Section: Conjunct Verb Constructionmentioning
confidence: 99%